RANCANG BANGUN KOMPUTERISASI SISTEM INFORMASI PENGIRIMAN BARANG PADA CV. SDC SENTUL BERBASIS JAVA - Dona Katarina; Muslihatul Hidayah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
CV. SDC is a subsidiary of the holding company, namely PT Mega Karya Mandiri or widely known by the public as PT Cargloss which is engaged in the helmet manufacturing industry. Today the application of an Information System made to facilitate the management and storage of data is needed because it can produce precise and accurate information, making the goods delivery system easier to understand and making reports. The existence of a precise and accurate information system can reduce the occurrence of unwanted errors so that it can improve company and employee performance to be more effective and efficient. Delivery data can also be processed in a more systematic, structured, transparent and honest way.